HUBUNGAN KECEMASAN DENGAN KELANCARAN PENGELUARAN ASI PADA IBU POST PARTUM DI WILAYAH KERJA PUSKESMAS PASIRJAMBU TAHUN 2024 - Rosmiati, Tita; Meliyanti, Mira (Sekolah Tinggi Ilmu Kesehatan Dharma husada, 2024)
Background: Breast milk production is the milk that comes out, marked by the release of colostrum during pregnancy and after delivery. The smooth production of breast milk is greatly influenced by psychological factors that need to be considered, such as anxiety. Research Objective: To determine the relationship between anxiety and the smooth flow of breast milk in post partum mothers in the Pasirjambu Community Health Center Working Area. Research Method: This study used a cross-sectional design. Data was collected in June 2024 from 36 respondents using total sampling techniques and questionnaires. Research Results: Smooth breast milk production is in the non-smooth category (83.3%). Statistical tests show that there is a significant relationship between the level of anxiety and the smooth flow of breast milk (p-value 0.000). Conclusion: There is a significant relationship between the level of anxiety and the smooth flow of breast milk in post partum mothers in the Pasirjambu Community Health Center Working Area. Suggestion: Post Partum mothers are expected to always be diligent in carrying out breast care starting before planning a pregnancy, to always be diligent in carrying out lactation massage after a few days of giving birth and to always be happy to reduce anxiety and facilitate the release of breast milk.